2010
DOI: 10.1016/j.resp.2010.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular determinants of maximal oxygen consumption in upright and supine posture at the end of prolonged bed rest in humans

Abstract: We tested the hypothesis that, after bed rest, maximal oxygen consumption ( VO₂max ) decreases more upright than supine, because of adequate cardiovascular response supine, but not upright. On 9 subjects, we determined VO₂max and maximal cardiac output (Q ) upright and supine, before and after (reambulation day upright, the following day supine) 35-day bed rest, by classical steady state protocol. Oxygen consumption, heart rate (f(H)) and stroke volume (Q(st)) were measured by a metabolic cart, electrocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 48 publications
3
34
0
4
Order By: Relevance
“…Direct experimental assessment of the parameters of Eq. (4.13) confirmed that F Q in normoxia is between 0.65 and 0.76 (Bringard et al 2010;Turner et al 1993). …”
Section: ð4:5þmentioning
confidence: 59%
See 4 more Smart Citations
“…Direct experimental assessment of the parameters of Eq. (4.13) confirmed that F Q in normoxia is between 0.65 and 0.76 (Bringard et al 2010;Turner et al 1993). …”
Section: ð4:5þmentioning
confidence: 59%
“…This component in fact was already visible, after the same time, in the study by Trappe et al (2006) in space and in supine posture after bed rest. Bringard et al (2010) found a 44 % reduction of stroke volume at maximal exercise in upright posture after 35-day bed rest as compared to the value before bed rest with no modification in maximal heart rate: the consequence was a 45 % decrease in maximal _ Q. This results, associated with a 13 % increase in CaO 2 due to higher haemoglobin concentration, originated a 38 % decrease in _ Q aO 2max .…”
Section: Of Maximal Oxygen Consumption At the End Of Bed Restmentioning
confidence: 70%
See 3 more Smart Citations